A AMÉRICA LATINA VISTA DO ALTO - Feres Jr., João (Revista de Sociologia e Política, 1999)
SCHOULTZ, L. Beneath the United States : a History of US Policy toward Latin America. London & Cambridge : Harvard University Press, 1998 (ISBN 067492276x; paperback: US$ 19,95)